PENGARUH PROFITABILITAS DAN SOLVABILITAS TERHADAP NILAI PERUSAHAAN INDEKS LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2019 - Wika Enrich Lamba; Paul Eduard Sudjiman (Jurnal Ekonomis, 2021)
This study aims to examine the effect of Profitability and Solvency on the Firm Value of the LQ 45 Index listed on the Indonesia Stock Exchange for the 2017-2019 period. This study uses quantitative methods obtained from the annual reports and financials of LQ 45 companies. The population in this study is LQ 45 companies indexed on the Indonesia Stock Exchange. The research sample consisted of 33 LQ 45 companies that survived during the 2017-2019 period. The results in this study indicate that profitability has a positive effect on firm value with sig. 0.000 < 0.05 and Solvency has a positive effect on Firm Value with sig. 0.014 < 0.05.